Within-Item Variation: A Stochastic Approach to Audit Uncertainty-A Reply. - Barkman, Arnold I. (The Accounting Review, 1978)
The article presets a reply from Arnold I. Barkman on the comment made by Richard K. Burdick and J. Hal Reneau on topics related to Within-Item Variation: A Stochastic Approach to Audit Uncertainty. Barkman assumes that the value that ultimately is associated with an item is not necessarily a fixed constant. He believes that measurement error and within-item variation are distinct concepts. Differing assumptions regarding whether values are fixed lead to differing perceptions of what an auditor sees when looking at an item. These differences also lead to differing definitions of terms that symbolically appear the same. Measurement error arises when repeated measurements of the same item yield different values. Barkman believes that the exchange of views regarding the nature of values has clarified some of the assumptions underlying his article. However, Barkamn do not believe that what Burdick and Reneau have done has resulted in a refinement of his approach, since their formulation reflects a view of the nature of values much different from that of Barkman.